The effect of anaesthetic exposure in presurgical period on delayed cerebral ischaemia and neurological outcome in patients with aneurysmal subarachnoid haemorrhage undergoing clipping of aneurysm: A retrospective analysis - Rajeeb K Mishra; Mihir P Pandia; Subodh Kumar; Gyaninder P Singh; M Kalaivani (Indian Journal of Anaesthesia, 2020)
Background and Aims: Delayed cerebral ischaemia is one of the major contributors to morbidity in aneurysmal subarachnoid haemorrhage (aSAH). General anaesthesia (GA) in the presurgical period may have a preconditioning effect. The primary aim was to assess the effect of preoperative exposure to GA during digital subtraction angiography (DSA) on neurological outcome in patients presenting with aSAH. Methods: After Ethical Committee approval, we conducted a retrospective analysis of the data of patients with aSAH treated surgically. Patients, admitted to neurosurgical ICU (June 2014 and December 2017) with a computed tomography (CT) diagnosis of aSAH and underwent DSA, were included. DSA, done with or without exposure to a general anaesthetic, was classified to GA group and LA group, respectively. Propensity score matching was done on the baseline variables. Appropriate statistical methods were applied. Results: Of the 278 patients, 116 (41.7%) patients had received GA during DSA. Propensity matching yielded 114 (57 in each group) matched patients. In a logistic regression model, the odds ratio (OR) for poor outcome at discharge in GA group as compared to LA group was 4.4 (CI: 2.7–7.4), P = 0.001, whereas, in the matched data, the OR for poor outcome at discharge in GA group as compared to LA group was 1.2 (CI: 0.6–2.6), P = 0.57. Conclusion: The presurgical exposure to GA did not offer any neuroprotection and the odds of poor outcome were higher compare to non-exposure to GA group.